Urgency Of Coal Mining Law Reform Based On The Principle Of Natural Benefits For Community Welfare And Environmental Sustainability - Erwanto, Runik (Jurnal sosial dan sains, 2025)
Coal mining as a strategic sector in national development in Indonesia often causes conflicts between economic interests, public welfare, and environmental sustainability. The existing mining legal system is considered not to have fully accommodated the principle of fair use of nature. The principle of natural benefit emphasizes that natural resources must be utilized as much as possible for the welfare of the people while maintaining their sustainability. Therefore, it is necessary to reform mining law that is not only oriented towards economic growth, but also pays attention to social justice and environmental sustainability as an implementation of Article 33 paragraph (3) of the 1945 Constitution. This study uses a normative legal method with a conceptual and philosophical approach, through an analysis of laws and regulations, legal doctrines, and relevant scientific literature. The results of the study indicate that reforming coal mining law based on the principle of natural benefit can encourage the creation of a balance between the interests of the state, society, and the environment in a sustainable manner.